¿Por qué hablar de la mente? - Hierro-pescador, José (Revista de Filosofía, 2007)
Attempting to escape from the substantialist cartesian dualism, some take our conceptual schemes as dualist. Thus, Feigl makes the distinction between the mental and the physical from an epistemological viewpoint, accepting as distinctive of the mental a direct and immediate knowledge which has no place in the physical, but however he accepts the identity between mental states and neurological states. In a similar way, Davidson, stating that all events are physical, characterizes the mental as a specific manner of describing neurological events, which is also accepted by Quine in his latest books. I take that theory as implying that there are mental properties, like those defined by Searle as macroproperties of the brain. But I see no reason to talk about the mind, unless with the purpose of abbreviating more complex expressions like ‘the set of mental properties’, or perhaps ‘the set of human psychological capacities’, as Kenny proposes.